2008
DOI: 10.1111/j.1365-2966.2008.13254.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarized infrared emission from X-ray binary jets

Abstract: Near-infrared (NIR) and optical polarimetric observations of a selection of X-ray binaries are presented. The targets were observed using the Very Large Telescope and the United Kingdom Infrared Telescope. We detect a significant level (3σ ) of linear polarization in four sources. The polarization is found to be intrinsic (at the >3σ level) in two sources; GRO J1655−40 (∼4-7 per cent in the H and K s bands during an outburst) and Sco X-1 (∼0.1-0.9 per cent in the H and K bands), which is stronger at lower freq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 67 publications
1
54
0
Order By: Relevance
“…The observations and results are summarized in Table 1; this work was published in [32]. Most sources were in quiescence, and no polarization was detected.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The observations and results are summarized in Table 1; this work was published in [32]. Most sources were in quiescence, and no polarization was detected.…”
Section: Introductionmentioning
confidence: 95%
“…Very recently, evidence for polarization intrinsic to the emitting photons of LMXBs has been revealed from infrared observations [40,32]. Shahbaz et al (2008) [40] performed infrared spectropolarimetry of three LMXBs and found two of them (the NSs Sco X-1 and Cyg X-2) to be intrinsically polarized, with an increasing linear polarization (LP) at lower frequencies (up to ∼ 2% in Sco X-1 and ∼ 10% in Cyg X-2).…”
Section: Introductionmentioning
confidence: 99%
“…The radiation emitted from a leptonic jet has a synchrotron nature, which is known to be intrinsically linearly polarised up to tens of per cent. Even in this case, because of the presence of strongly tangled magnetic fields in the jet, radiation is expected to be polarised at a few per cent at most, mainly at lower frequencies (the radio and infrared bands; Russell & Fender 2008). …”
Section: Based On Observations Made With European Southern Observatormentioning
confidence: 99%
“…The only evidence of ordered magnetic fields in LMXBs jets has been observed for the persistent system Cyg X-1 (Russell & Shahbaz 2014). Only a few LMXBs have been observed with polarimetric techniques to date, both persistent and transient ones (Charles et al 1980;Dolan & Tapia 1989;Gliozzi et al 1998;Hannikainen et al 2000;Schultz et al 2004;Brocksopp et al 2007;Shahbaz et al 2008a;Russell & Fender 2008;Russell et al 2011;Baglio et al 2014).…”
Section: Polarimetric Signatures Of a Jetmentioning
confidence: 99%